Pengaruh Pemberian Jus Wortel Terhadap Penurunan Dismenore Pada Remaja Putri di SMP Muhammadiyah 2 Wonosobo, Lampung - Dwi Eka Oktaviyani; Rina Sri Widayati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background; In Lampung province, the incidence of dysmenorrhea is quite high, the results of the study found that 54.9% of women experience it. Dysmenorrhea is lower abdominal pain that sometimes extends to the waist, lower back and thighs, caused by high production of prostaglandins then stimulates the uterus to contract. The most common impact of dysmenorrhea is limited physical activity and poor concentration, so it must be addressed immediately so as not to further interfere with daily activities. One of the non-pharmacological treatments is by drinking carrot juice where carrots contain vitamin E and beta-carotene which can suppress prostaglandin production so that it can reduce the pain experienced. Objective; To determine the effect of carrot juice on reducing dysmenorrhea in adolescent girls at JHS Muhammadiyah 2 Wonosobo, Lampung. Method; This type of research is quantitative research with a pre-experimental design with a one group pretest and posttest design approach, the population is 28 respondents, the number of samples is 22 respondents with Simple Random Sampling technique. Data collection tools using observation sheets, data analysis with Wilcoxon test ? = 0.05. Results; The results of observations for 1 day with a frequency of 2x a day obtained a p-value of 0.000 where 0.000 <0.05 this means H0 is rejected and Ha is accepted. Conclusion; There is an effect of giving carrot juice on reducing dysmenorrhea in adolescent girls at JHS Muhammadiyah 2 Wonosobo, Lampung.